Tooth-Bone-Borne Vs. Bone-Borne Palatal Expanders: A Systematic Review - Yacout, Yomna M.; Hassan, Mohamed G.; El-Harouni, Nadia M.; Ismail, Hanan A.; Zaher, Abbas R. (Frontiers in Dental Medicine, 2021)
The aim of this review was to evaluate the current evidence regarding post-treatment effects of tooth-bone-borne vs. bone-borne expanders. A search was conducted in MEDLINE via PubMed, Web of Science, Scopus, Cochrane Library, Google Scholar, and Open Gray; in addition to a hand search in reference lists of selected articles and creating a search alert in electronic databases. Selection criteria included randomized and prospective clinical trials comparing post-expansion skeletal and/or dento-alveolar effects of tooth-bone-borne expanders to those of bone-borne expanders. Following study retrieval and selection, relevant data was extracted, and risk of bias was assessed using the revised RoB 2 tool for randomized clinical trials. After examining 10 full text articles, one randomized clinical trial was finally included. The study compared the dento-alveolar effects of tooth-bone-borne and bone-borne expanders, following expansion and after 6 months, using digital dental casts. Using the RoB 2 tool, the study was judged overall to show some concerns. A definitive conclusion could not be drawn from this systematic review due to the scarcity of clinical trials tackling the research question. A need for future well-conducted research was highlighted in this review.